Extraction of oil from jatropha seeds-optimization and kinetics - Sayyar, Sepidar; Zainal Abidin, Zurina; Yunus, Robiah; Muhammad, Azhari (Science Publications, 2009)
Problem statement: Jatropha curcas is a wonder plant with a variety of applications and enormous economic potentials. Oil from the seeds can be used as alternative fuel and for making biodiesel which aims to overcome energy crisis problems. In this study, extraction of Jatropha oil from seeds was optimized using organic solvent based on the amount of the extracted oil. The kinetics of extraction was also investigated and its parameters were determined based on a second order model. Approach: The effects of five operating parameters on the oil extraction namely type of solvents, temperature, solvent to solid ratio, processing time and particle size of the meal were investigated to optimize the processing conditions for achieving maximum oil yield. The kinetics of extraction was assumed based on a second order mechanism. The initial extraction rate, the saturated extraction capacity, the rate constant of extraction and the activation energy were calculated using the model. Results: The optimum conditions were found at 8 h reaction time, temperature of around 68°C, coarse particle size (0.5-0.75 mm), solvent to solid ratio of 6:1 and hexane as solvent. The activation energy was found to be 8021.9 J moL−1. Conclusion: Hexane was found to be the best solvent for the process as compared to petroleum ether, the kinetics of extraction conforms well to the second order model and the extraction of Jatropha seeds was an endothermic process.